PENGARUH TIM KERJA, BUDAYA ORGANISASI, DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI Studi Kausal di PT. Indah Cup Sukses Makmur - Joko Supriyanto; Ahmad Faisal (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2021)
Abstract This objective of this research is to study the effect of the work team, organization culture, and job satisfaction on the organization commitment. This research was conducted at PT. Indah Cup Sukses Makmur, Bogor, West Java. the method used to analyze this research is the causal study or path analyze. The sample of this research were 110 employee, and at selected randomly.The research result showed, there is effect positive and significant work team on job satisfaction, there is effect positif and significant organization culture on job satisfaction, there is effect work team on commitment organization, there is effect positive and significant organization culture on commitment organization, there is effect positif and significant job satisfaction on commitmen organization.Best on the result of the reseacrh, can be concluded that the commitment organization were effect by work team, organization culture, and job satisfaction employees. Keywords: Work team, organization culture, job satisfaction, commitment organization